Territory and governance: an analysis of the Beer Sector Chamber in Brazil - Marcusso, Eduardo Fernandes; Eudâmidas Bezerra, Juscelino (Geografares, 2024)
This article aims to analyze the territorial governance of the beer sector in Brazil through the establishment of the Beer Sector Chamber. The methodology involved a literature review on the concepts of territory, governance, and development; an examination of the legal framework of Sector Chambers; a historical analysis of power disputes; and the framing of the territorial governance of the beer sector according to the research methodology. Additionally, interviews were conducted, and participation in the chamber’s meetings was undertaken. The findings reveal the formation of socio-territorial blocs around the beer sector and their role in negotiation, sharing, agreements, consensus-building, and power struggles, resulting in specific configurations of networked territorial governance through the Beer Sector Chamber.